When does consciousness arise? A subcortical model of its origins - Saúl Sal-Sarria; Mark Solms; Oliver H. Turnbull (Brain Structure and Function, 2026)
The origin of consciousness constitutes one of the most enduring challenges in contemporary science, with implications for neuroscience, philosophy, medicine and ethics. Traditional accounts have emphasized the cerebral cortex as the seat of conscious awareness, largely due to its expansion and complexity in humans. However, converging evidence suggests that the foundations of consciousness lie not in higher cognition, but in more ancient subcortical systems responsible for affective experience. Central among these are the ascending arousal networks of the upper brainstem and the periaqueductal gray, which together sustain wakefulness and imbue it with valence. This reframing positions consciousness as an embodied biological function grounded in feeling, rather than as a component of higher cognition. From a developmental perspective, the relevant subcortical structures mature relatively early in gestation, raising the possibility that a primitive form of subjective feeling may emerge during the third trimester, well before cortical maturation. Such a view has far-reaching ethical consequences, informing debates on fetal pain perception, neonatal care, and the treatment of individuals with profound cognitive impairment. By synthesizing recent neuroscientific findings with developmental data, this paper argues for a subcortical basis of consciousness, and highlights the need for an integrative approach that situates the origins of consciousness within affective brainstem systems.

Testosterone administration in women increases the size of their peripersonal space - Catherine Masson; Donné van der Westhuizen; Jean-Paul Noel; Adala Prevost; Jack van Honk; Aikaterini Fotopoulou; Mark Solms; Andrea Serino (Experimental Brain Research, 2021)

A linkage and family-based association analysis of a potential neurocognitive endophenotype of bipolar disorder - Jonathan Savitz; Lize van der Merwe; Mark Solms; Rajkumar Ramesar (NeuroMolecular Medicine, 2007)

A linkage and family-based association analysis of a potential neurocognitive endophenotype of bipolar disorder - Jonathan Savitz; Lize Merwe; Mark Solms; Rajkumar Ramesar (NeuroMolecular Medicine, 2007)